The narrative within the interactive documentary for the reconstruction of memory: enforced disappearances in Latin America - Borja, Lupe Martinez (2022)
The exposure of social problems such as forced disappearances is necessary for the history of society. The interactive documentary is a new digital proposal for the creation of spaces for the reconstruction of a social memory. In this paper, a content analysis is used to analyze the construction of the interactive narrative for the reconstruction of memory in the webdoc Forensic Landscapes and, with this, to identify its narrative composition in the construction of new spaces for the user’s experience. The interactive documentary generates a shared feeling between the user and the interface due to resources such as hypertextuality, database, narrative elements, representation modalities and interactivity. Thus, immersion is adhered, a new way of exposing a social theme in 360 degrees which recreates a sensory experience within an imaginary universe. Through the story, the memory of the agents involved in forced disappearances in Latin America is reconstructed.